PELESTARIAN HUTAN MANGROVE BERBASIS MASYARAKAT DAN STRATEGI PENGURANGAN RISIKO BENCANA DI KAMPUNG APAINABO DISTRIK UREI FASEI KAB. WAROPEN – PAPUA - Mercyana Trianne Zebua (Jurnal PORTAL SIPIL, 2017)
Mangrove is one of the main ecosystems found in the coastal area. From around 15.9million ha of mangrove forest in the world, approximately 27% are located in Indonesia. Morethan that, mangrove forests is one of the unique natural ecosystems, and it has very highecological and economical value. In 2010, Apainabo Village in District Urei Fasei Regency ofWaropen that is located in the coastal area has 5,672.85 ha area of mangrove forests. However,due to the damage of the mangrove forests in 2016, the extensive area of mangrove forests hasturned into 3,977 ha or it has decreased by 30%.This then led to an increasingly frequent floodingat Apainabo village in the event of a tidal wave. Forest damage often caused more by villagers’activities such as logging for firewood. To take care of the problem or this damage situation, wehave to do a rehabilitation of mangrove forests which are part of the management of mangroveforests by engaging the community. The main purpose of doing mangrove managementcommunity-based is to improve the welfare of the communities surrounding the mangrove forestsarea. The management and preservation of mangrove forests can be conducted with two mainconcepts. These two concepts are basically needed to give a legitimacy and an understanding thatthe mangrove forest needs a protection and a management so that mangrove ecosystems canremain sustainable. The two concepts are protection of mangrove forests and the rehabilitationof mangrove forests.